Microalgae strains selection and medium constituents optimization to enhance calcium carbonate biomineral precipitation by Chlorella vulgaris and Synechocystis sp. ATCC 27178 - Arumugam, Kavithraasshre (2022)
Rapid urbanisation has led to accelerated consumption of concrete. Portland Cement, a key binder in concrete is the most used human-made materials contributing to anthropogenic CO2 emission. Alternatively, microbially-mediated construction processes and materials could pave ways to more sustainable routes based on the biomineralization process. Precipitation of mineral carbonates by certain microorganisms’ metabolic activities can improve the behaviour of concrete or create new construction material. In this study, the potential of eight microalgae strains to undergo calcium carbonate (CaCO3) precipitation to produce cementitious biomineral were assessed, in a process commonly termed as microbially-induced calcium carbonate precipitation (MICP). Initially, these microalgae were cultivated in a medium containing 12 mM CaCl2.2H2O and 0.18 to 5.0 mM NaHCO3 and measured for pH, cell growth, calcium concentrations and total alkalinity. Chlorella vulgaris and Synechocystis sp. ATCC 27178 registered the highest apparent precipitation rate at 0.7 and 0.4 mM/day, respectively, in 5.0 mM NaHCO3 medium. Morphological examination of CaCO3 deposit by SEM-EDX and XRD confirmed it as calcite crystalline structure. These strains were also screened for urease, which catabolises urea as the additional substrate for cell growth and carbonate source for MICP. Consequently, strains having urease activity were cultured in BG-11 medium fixed with 12 mM CaCl2.2H2O and 5 mM NaHCO3 but at varying urea concentrations (0 to 0.4 g/L) to investigate urea’s effect on CaCO3 precipitation. Carbonic anhydrase and urease activity were assayed, of which, C. vulgaris produced the highest precipitation at 0.30 g/L (in 0.2 g/L urea-containing medium) with highest specific urease (SU) activity of 0.127 U/mg/min (on day 2). Synechocystis sp. produced 0.411 g/L of CaCO3 (in 0.15 g/L urea-containing medium) with the highest SU of 0.317 U/mg/min (also on day 2). Enhancement to the modified BG-11 (with 12 mM CaCl2.2H2O and 5 mM NaHCO3) with urea at 0.2 g/L (C. vulgaris) and 0.15 g/L (Synechocystis sp.) was achieved through Plackett-Burman Design (PBD), followed by Steepest Ascend Method to search for an effective range, and optimised by Response Surface Method (RSM). PBD screening indicated three significant variables, i.e., NaNO3, NaCH3COO and K2HPO4 and two positive variables: NaNO3 and NaCH3COO, affecting the response in C. vulgaris and Synechocystis sp., respectively. Validating the prediction by RSM, modified BG-11 medium optimized with NaCH3COO (39.5 mM), K2HPO4 (0.32 mM) and NaNO3 (19.25 mM) exhibited a productivity of CaCO3 precipitation at 81.6 mg/L/day. It was a 279% improvement over C. vulgaris cultivation using modified BG-11 medium fixed with 12 mM of CaCl2.2H2O, 5 mM of NaHCO3 and 0.2 g/L of urea. For Synechocystis sp., by setting NaCH3COO (60.04 mM) and NaNO3 (0.57 mM), this led to the productivity of 83 mg/L/day. It was 183% more improvement against Synechocystis sp. cultivated under identical pre-optimized modified BG-11 medium conditions as C. vulgaris but with 0.15 g/L of urea.